Gender Asymmetry of Small Business (on the Example of Moscow) - M. E. Baskakova (Мир новой экономики)
The article examines trends, problems and prospects for broader involvement in entrepreneurship of women as the most professionally educated part of the country’s manpower, which could, on the one hand, impart the necessary dynamics to the business development process, and, on the other hand, expand opportunities and flexibility of professional employment of women themselves. The purpose of the article is to analyse the existing gender asymmetry of the parameters of Russian entrepreneurship and their characteristics in the capital, to identify gender differences in the barriers that entrepreneurs face in their work, to assess the possibilities and conditions for expanding employment of women in small and medium businesses. The work is based on data from Rosstat, obtained in the framework of projects “Population survey on employment problems” and “Comprehensive monitoring of living conditions of the population”, as well as from a survey of Moscow population engaged in small business, which was conducted by the Institute of Economics of the Russian Academy of Sciences in 2015. The author showed that barriers faced by entrepreneurs in their activities are not discriminatory, and the differences in expectations for government support, demonstrated by male and female entrepreneurs, mainly reflect the difference in the size of their business and segregation of the business by economic activity.